Proceedings of the 16th Annual International Conference on Digital Government Research 2015
DOI: 10.1145/2757401.2757412
|View full text |Cite
|
Sign up to set email alerts
|

The effects of technology use on efficiency, transparency, and corruption in municipal governments

Abstract: The idea that government transparency is directly related to the use of technology was boosted when Barack Obama's Transparency Memorandum was published in 2009. According to this view, the implementation of information technologies in government has significant effects on efficiency, transparency, and corruption, among other variables. However, it is not clear if citizens perceive these effects. Based on a pilot survey conducted in 2014, this study systematically examines the role of technology use and its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Next to e-government, Porumbescu (2016b) showed that the use of public sector social media accounts increases citizens' satisfaction and perception of public sector trustworthiness. Additionally, Valle-Cruz et al (2015) highlight the positive effects of online-based citizen-government collaboration on citizens' perceptions of transparency and efficiency.…”
Section: Hypothesesmentioning
confidence: 98%
“…Next to e-government, Porumbescu (2016b) showed that the use of public sector social media accounts increases citizens' satisfaction and perception of public sector trustworthiness. Additionally, Valle-Cruz et al (2015) highlight the positive effects of online-based citizen-government collaboration on citizens' perceptions of transparency and efficiency.…”
Section: Hypothesesmentioning
confidence: 98%
“…The study by Cardenas et al (2012) which compared countries in three-world regions (Eastern Europe, Southeast Asia and Central American/Caribbean) over a 20-year period, conclude that geographical location, financial status social infrastructure and governance mechanism impacts the rate at which ICT applications are diffused. Although Baliamoune-Lutz (2003) found that income and government trade policies influence ICT diffusion; Valle-Cruz et al (2015) found that interactions between citizens and government supported by emergent technologies helped to improve citizens' perceptions of transparency and efficiency and continued reliance on those technologies.…”
Section: Ijotb 222mentioning
confidence: 99%
“…There is growing attention among city councils in developing countries to incorporate location and spatial knowledge in their procedures for decision-making [40,41]. These cities have primarily utilized Information and Communication Technology (ICT) and social media [41,42] to make cities smarter [43]. According to McCall and Dunn [26], Geo-ICT enables citizens in translating spatial concepts of reality and their knowledge of phenomena into maps.…”
Section: Voluntary Geographic Information (Vgi) In Urban Planning Monmentioning
confidence: 99%